Hubungan antara kebiasaan olahraga dengan dismenore primer pada mahasiswi pre-klinik Program Studi Pendidikan Dokter Fakultas Kedokteran Universitas Udayana tahun ajaran 2017 - Ketut Anita Herdianti; Nyoman Gede Wardana; I Nyoman Mangku Karmaya (Department of Anatomy, Medical Faculty, Universitas Udayana, Bali-Indonesia, 2019)
Primary dysmenorrhea is defined as a painful sensation during menstruation that is not associated with gynecological disorders or without the discovery of a pathological condition in the pelvis. Primary dysmenorrhea is the most common type of menstrual pain, which is experienced by more than 50% of women, so effective prevention with minimal side effects is needed, such as improvement in exercise habits. This study aims to determine the relationship between exercise habits with primary dysmenorrhea in female students of the Faculty of Medicine Unud academic year 2017. The type of research used is observational analytic with a cross sectional approach. The research subjects were 96 students from the Faculty of Medicine Unud academic year 2017. The research data were primary data in the form of questionnaires. Of the 96 samples examined, most of the students experienced primary dysmenorrhea with a proportion of primary dysmenorrhea is 86.5% and respondent with routine exercise habits less than respondent whose exercise habits were not routine with a proportion of 12.5% and 87.5% each. Students with regular exercise habits found a higher proportion of primary dysmenorrhea, 75% compared to 25% without primary dysmenorrhea. Based on the results of the chi-square test showed that there was no significant relationship between exercise habits with primary dysmenorrhea in Pre-Clinical Students of Medical Education Program Faculty of Medicine Udayana University Academic Year 2017 with p-value = 0.215.